Proposal for a regulation on health technology assessment in Europe – opinions of policy makers, payers and academics from the field of HTA. (4th May 2019) - Vella Bonanno, Patricia; Bucsics, Anna; Simoens, Steven; Martin, Antony P; Oortwijn, Wija; Gulbinovič, Jolanta; Rothe, Celia; Timoney, Angela; Ferrario, Alessandra; Gad, Mohamed; Salem, Ahmed; Hoxha, Iris; et al.
ABSTRACT: Introduction: In January 2018 the European Commission published a Proposal for a Regulation on Health Technology Assessment (HTA): 'Proposal for a Regulation on health technology assessment and amending Directive 2011/24/EU'. A number of stakeholders, including some Member States, welcomed this initiative as it was considered to improve collaboration, reduce duplication and improve efficiency. There were however a number of concerns including its legal basis, the establishment of a single managing authority, the preservation of national jurisdiction over HTA decision-making and the voluntary/mandatory uptake of joint assessments by Member States. Areas covered: This paper presents the consolidated views and considerations on the original Proposal as set by the European Commission of a number of policy makers, payers, experts from pricing and reimbursement authorities and academics from across Europe. Expert commentary: The Proposal has since been extensively discussed at Council and while good progress has been achieved, there are still divergent positions. The European Parliament gave a number of recommendations for amendments. If the Proposal is approved, it is important that a balanced, improved outcome is achieved for all stakeholders. If not approved, the extensive contribution and progress attained should be sustained and preserved, and the best alternative solutions found.